2020
DOI: 10.1021/acsphotonics.0c00148
|View full text |Cite
|
Sign up to set email alerts
|

Controlling Quantum Pathways in Molecular Vibrational Polaritons

Abstract: Molecular vibrational polaritons, hybrid quasi-particles formed by molecular vibrations and cavity photons through strong light−matter coupling, have attracted much attention due to their potential to alter photonic properties and to change the course of chemical reactions. The ultrafast dynamics of molecular vibrational polaritons have been studied to advance our understanding of these interesting hybrid quasiparticles. For example, the roles of dark states, hot vibrational mode relaxation in cavities, and ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
54
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 32 publications
(55 citation statements)
references
References 34 publications
1
54
0
Order By: Relevance
“…4). Previous reports have shown early time oscillations 19 , and very recently, Yang, et al confirmed that the oscillations arise from coherence exchange between modes 24 . By using half-pump pulses, as described above, we were able to suppress the early time oscillations of cavity-coupled SNP and recover the oscillations when exciting both polaritons with a broadband pulse.…”
Section: Nonlinear Spectroscopy Of Cavity-coupled Snpmentioning
confidence: 81%
See 4 more Smart Citations
“…4). Previous reports have shown early time oscillations 19 , and very recently, Yang, et al confirmed that the oscillations arise from coherence exchange between modes 24 . By using half-pump pulses, as described above, we were able to suppress the early time oscillations of cavity-coupled SNP and recover the oscillations when exciting both polaritons with a broadband pulse.…”
Section: Nonlinear Spectroscopy Of Cavity-coupled Snpmentioning
confidence: 81%
“…Selective pumping is an established technique 24,49,50 which we implement in the 2D IR apparatus via a pulse shaper. The pulse shaper disperses the pump beam in frequency across the AOM.…”
Section: Pump Filtering Methodsmentioning
confidence: 99%
See 3 more Smart Citations